Detection of tACS Entrainment Critically Depends on Epoch Length - Mc Laughlin, Myles; Khatoun, Ahmad; Asamoah, Boateng (Frontiers in Cellular Neuroscience, 2022)
Neural entrainment is the phase synchronization of a population of neurons to an external rhythmic stimulus such as applied in the context of transcranial alternating current stimulation (TACS). TACS can cause profound effects on human behavior. However, there remain a significant number of studies that find no behavioral effect when TACS is applied to human subjects. To investigate this discrepancy, we applied time sensitive phase lock value (PLV) based analysis to single unit data from the rat motor cortex. The analysis revealed that detection of neural entrainment depends critically on the observation windowepoch length within which spiking information is accumulated. Increasing the observation windowepoch length allowed for detection of progressively weaker levels of neural entrainment. Based on this single unit analysis, we hypothesized that TACS effects on human behavior would be more easily detected in a behavior paradigm which utilizes longer epoch lengths. We tested this by using TACS to entrain tremor in patients and healthy volunteers. When the behavioral data were analyzed using short duration epochs tremor entrainment effects were not detectable. However, as the epoch length was progressively increased, weak tremor entrainment became detectable. These results suggest that TACS behavioral paradigms that rely on the accumulation of information over long epoch lengths will tend to be successful at detecting behavior effects. However, TACS paradigms that rely on short epoch lengths are less likely to detect effects.